Gender integration in livestock and fisheries value chains: Emerging good practices from analysis to action - Farnworth, Cathy Rozel; Kantor, Paula; Kruijssen, Froukje; Longley, Catherine; Colverson, Kathleen E. (Inderscience Publishers, 2015)
It is widely recognized that women are significant actors in crop-livestock, pastoralist and fish systems. However, too little is known about agricultural development projects which deliberately work towards gender equity in livestock and fish value chains. Research insights into gender roles and responsibilities along fish and livestock chains on how gender relations at household and community level may affect women and men's access to resources for livestock production, and their relative benefits from value chain development, are often weakly integrated into development planning and practice. More profoundly, inequalities tend to reproduce inequalities. These are crippling for the individuals involved as well as for the achievement of development outcomes. In order to redress the balance a number of research and development partners are working to develop analytic frameworks and implementation guidelines to enable gender equity in livestock and fish value chains. This paper examines recent and on-going work to develop tools for effective gender analyses in value chains and how these are being fed into project design. Case studies are taken from Zambia, Kenya and Egypt.